Una aproximación descriptiva a la propiedad intelectual de bajo valor agregado y distorsión de la competencia: Caso Estados Unidos (2016)
This research paper analyzes the disadvantages of patenting low added value inventions considered obvious on the operation of the free market under the free market theoretical perspective for the U.S case. Gaps are strong in relation to considered obvious inventions which discourages business innovation as a result of imperfect information flow limiting knowledge of existing patents. Also discourage competition from small and micro enterprises who choose to go the legal system to maintain market share. The analysis method is based on data research form different official sources.